The experiences of community college transfer students returning from academic suspension at a four-year research institution - Carter, Carmen R., author; Carlson, Laurie, advisor; Davies, Timothy, committee member; Kuk, Linda, committee member; Newman, Peter, committee member (Colorado State University. Libraries, 2013)
More students are beginning their higher education journey at community colleges with the intent of transferring to a four-year college or university. The purpose of this study was to attempt to gain a better understanding of the experiences of two-year community college transfer students who transferred to a large, four-year public research university, experienced academic difficulty which resulted in academic suspension, and returned to successfully persist towards a baccalaureate degree. The study used a qualitative, narrative inquiry research design to answer research questions related to how critical events in the lives of four community college transfer students affected their persistence at a four-year institution. A series of in-depth interviews allowed participants to share their experiences surrounding barriers to persistence, critical events which occurred during their suspension period, and factors that facilitated their persistence towards baccalaureate degree attainment once they returned from academic suspension. The narratives of the participants were analyzed using holistic content analysis to give further voice to the challenges the participants faced in their higher education journey. Four emergent themes developed across the participant narratives which were (a) Reluctance in Seeking Support, (b) Familial Influence, (c) Perseverance, and (d) Maturation. A discussion of the findings of this study indicated several implications for practice including an understanding that interventions for students facing academic difficulty must be invasive, realistic, yet hopeful, and assessed regularly for effectiveness.
Keywords: degree attainment; academic suspension; higher education; persistence; transfer students